Impact of Work Engagement and Social Capital on Employee Performance and Organization Commitment as an intervening - Permono Nugroho, Sidiq; Suharnomo, Suharnomo; Mahfudz, Mahfudz (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
A company's most valuable asset is its workforce, and a successful workforce is the cornerstone of any business. Retaining productive and high-performing employees who can assist the company in reaching its goals and objectives while competing globally is a challenge for modern businesses. The study is to measure the influence of job involvement and social capital on employee performance using organisational commitment as a mediating variable. One hundred participants completed an online survey using a Google form as part of this study. The sampling process made use of purposeful sampling. Use intelligent PLS analysis to assess the reliability and validity of the outer model. Hypotheses are tested using the smartPLS inner and outer models. The results showed that organisational commitment, work involvement, and social capital all had favourable and significant effects on employee performance. Furthermore, the positive and noteworthy impacts of social capital on employee performance are partially mediated by organisational commitment. the effect of social capital and job involvement on worker performance